You, being beautiful : the owner's manual to inner and outer beauty - Roizen, Michael F. (Free Press, 2008)
A guide to looking and feeling beautiful counsels readers on the connection between health and beauty while outlining scientifically valid recommendations for skin care, diet, stress management, alleviating pain, and achieving happiness.